До питання про навантажувальність одноразового вживання біоактивної води Нафтуся стосовно роботи серця - Флюнт, І.С.; Нестерова, Л.Ф.; Ковальський, С.В.; Іваницька, О.М.; Величко, Л.М.; Тимочко, О.Б.; Драновський, А.Л. (Медична гідрологія та реабілітація, 2008)
Показано, что через полчаса после однократного приема воды Нафтуся в 29,3% пациентов минутная работа сердца существенно (в среднем на 40%) увеличивается, в 25,0% пациентов нагрузочный эффект Нафтуси на сердце умеренный (увеличение в среднем на 13%), в 22,4% лиц минутная работа сердца практически не изменяется, а еще в 22,4% - достоверно уменьшается в среднем на 9%. It is shown, that in half an hour after unitary reception of water Naftussya in 29,3 % of the patients the minute work of heart is essential (on the average on 40 %) increases, in 25,0 % of the patients louding effect of Naftussya on heart moderate (increase on the average on 13 %), in 22,4 % of the persons the minute work of heart practically does not change, and in 22,4 % - significantly decreases on the average on 9 %.